(untitled) (Journal of the Management Sciences, 2024)
This study focused on conflict management and organizational performance on selected branches of First Bank of Nigeria, in Awka, Anambra. The specific objectives were focused on the relationship between collaboration strategy and work relationship among the employees; and between compromise strategy on and goal attainment; in the selected branches of First Bank of Nigeria, in Awka, Anambra. The study was anchored on Contingency Theory by Fiedler. The study adopted survey research design and simple random sampling technique was used to select the branches of first banks in Awka, Anambra State. The population of the study is 189 and Taro Yamane formula was used to determine the sample size of 128. Data were collected with the aid of structured questionnaire, while other data were analyzed using descriptive statistics (arithmetic mean). Findings revealed that there is positive relationship between conflict management and organizational performance in selected branches of First Bank Plc, Awka, Anambra State by indicating that there is positive relationship between collaboration strategy and work relationship; and between compromise strategy and goal attainment. The study concluded that conflict management technique of collaboration and compromise are effective and as such foster healthy work environment towards outstanding performance of the organization. Therefore, the study recommended that management should establish a platform where employees discuss grievances so as to treat errors on the tables before it results in conflict in the organization.